Comparative Effect Of Pseudomonas Fluorescens, Neem Seed Karnel Extract And Fungicide Against Powdery Mildew Of Sunflower (Journal of Plant Disease Sciences, 2018)
A field experiment with seven treatments of chemical fungicide difenoconazole, bio agents Pseudomonas fluorescens and neem seed kernel extract (NSKE) were assessed against powdery mildew of sunflower under field conditions at Oilseeds Research Unit, Dr. Panjabrao Deshmukh Krishi Vidyaeeth., Akola during Kharif 2012-13 to 2014-15. Result revealed that under field conditions fungicide difenoconazole was best effective in controlling the disease severity (11.67%), highest per cent disease control (83.46%) and highest ICBR 36.68 followed by NSKE @ 5ml/l at 45 + Difenoconazole 25 EC @ 2ml/l at 65 DAS (25.51%, 63.85% and 29.11) and P. fluorescens Coimbatore (29.11%, 58.74% and 16.01) respectively.
Keywords: Powdery mildew; sunflower; fungicide; bio agent; neem seed kernel extract